Revolutionizing Higher Education: Integrating the Academic Bank of Credits (ABC) with MOOCs for Personalized, Flexible Learning and Enhanced Skill Development - Hoque, Md Asraul (Indian Journal of Educational Technology, 2025)
The integration of the Academic Bank of Credits (ABC) and Massive Open Online Courses (MOOCs) aims to enhance flexibility, accessibility, and personalized learning in higher education. This study explores the experiences of Social Sciences students at the Central University of South Bihar with the ABC-MOOCs model, focusing on flexibility, workload management, content quality, technical challenges, and skill development. Using a mixed-methods approach, the study combines quantitative survey data with qualitative insights from open-ended responses and interviews. Findings indicate that while students appreciate the flexibility and personalized learning opportunities, challenges such as managing workloads, perceived lack of depth in some MOOCs, and technical issues hinder the model’s effectiveness. Concerns about limited interaction in MOOCs also emerged, affecting collaborative learning. Despite these issues, students reported positive outcomes in skill development, particularly in data analysis and practical applications. The study concludes that improvements are needed to optimize the integration of ABC-MOOCs, including enhanced course quality, better workload support, improved infrastructure, and increased interactivity. These measures can foster a balanced, enriching learning experience that meets students’ diverse academic and professional needs.